Exploring Frontiers of the Mind–Brain Relationship edited by Alexander Moreira-Almeida and Franklin Santana Santos - Matlock, James G. (Journal of Scientific Exploration, 2012)
The paradigm shift in physics that came with the establishment of quantum mechanics in the last century has implications for all the sciences, but that fact has been remarkably slow to sink in, perhaps in part because physicists themselves have not been able to agree on what it means. The one thing that seems incontrovertible is that quantum reality is qualitatively different from the everyday, observable macro-reality in which we commonly operate. At the level of the latter, Newtonian mechanics works well and supports a materialistic perspective, but underlying our quotidian world is a strange probabilistic sub-atomic world in which particles are waves and waves are particles and nothing is definite until it is viewed by an observer (or so some claim).